**Answer:**

3^10

**Step-by-step explanation:**

9^7 + 3^12

Replace 9 with 3^2

(3^2)^7 + 3^12

We know that a^b^c = a^(b*c)

3^(2*7) + 3^12

3^14 +3^12

Factor out 3^12

3^12 (3^2+1)

3^12 (9+1)

3^12(10)

But we need 90 not 10

3^10 * 3^2 (10)

3^10 *9 (10)

3^10 *(90)

**Answer:**

x = 27

**Step-by-step explanation:**

4(x−9)=4(9+1/3x).

Divide each side by 4

(x−9)=(9+1/3x)

Subtract 1/3 x from each side

x - 1/3x -9 = 9+1/3x -1/3x

2/3x -9 = 9

Add 9 to each side

2/3x -9+9 = 9+9

2/3x = 18

Multiply each side by 3/2

3/2 * 2/3x = 18*3/2

x = 27

Dude that’s correct

S=4(p + q)

S

– - q = p

4

S

– - q = p

4

s

p = – - q

4

The answer is D because at 2 hours, Kevin’s distance from home was 90 miles. Bill was at 110 miles after 2 hours.